2SPD-033 Impact of supply problems in a hospital pharmacy service. (March 2019) - Zarate, B; Pieras López, A; Carriles, C; Menarguez, R; Rodriguez, A; Arias, A; Maray, I; Alvarez, C; Iglesias, A; Zapico, I; Martinez, A
Abstract : Background: The hospital management of drugs is a complicated task for which it is necessary to take into account different factors such as average consumption, seasonal variations, cost, physical space available for storage and therapeutic innovations. Currently this task is hampered by the numerous supply issues (SI) that in many cases affect regular used drugs. These problems can lead to shortages and produce lack of effectiveness of treatments, compromise patient safety and increase treatment costs. Purpose: Analyse SI and their impact on the management of drugs in the pharmacy service of a hospital. Material and methods: Prospective study to evaluate the SI between June and August 2018 The variables collected were: start and end dates of the SI (end date of the study was 13 September 2018), the ATC code and if the drugs are considered essential by the World Health Organisation (WHO), if they produced shortages, if the SI affects all the providers and the possibility of an available alternative (same medication but different dose or different medication). An economic analysis of the SI is made with all the data registered in an Excel sheet. Results: There were 49 SI affecting 48 drugs, 25 of which remain active at the end of the period of study. The average duration was 37 days (range 2–104). Most affected therapeutic groups were: anti-infective (17%), anti-neoplasic (17%), nervous system (17%), blood and haematopoietic organs (13%) and cardiovascular system (13%). Fifty-three per cent of the affected drugs are considered essential by the WHO. In 23% of cases there was a stock shortage. In half of the cases there is a global shortage of the molecule, and in 71% there is an alternative that allows the change of drug. The total additional cost of supply problems was €38.511. Conclusion: SI makes it difficult to manage medicines at the pharmacy service and consumes a significant amount of resources so that they do not affect the patient. Shortages usually increase treatment costs. Considering that most of the supply problems are essential drugs, these problems can compromise the quality of healthcare and patient safety. References and/or acknowledgements: Agencia Española de Medicamentos y Productos Sanitarios, Centro de Inoformación de Medicamentos (CIMA) Disponible en:https://cima.aemps.es/cima/publico/home.html No conflict of interest.